Controllable Synthesis of Three-Dimensional Chiral Au Nanoflowers Induced by Cysteine with Excellent Biocompatible Properties - Shengmiao Liu; Jianhao Zhang; Wenjing Yan (Nanomaterials)
Chiral molecules are ubiquitous in nature and biological systems, where the unique optical and physical properties of chiral nanoparticles are closely linked to their shapes. Synthesizing chiral plasmonic nanomaterials with precise structures and tunable sizes is essential for exploring their applications. This study presents a method for growing three-dimensional chiral gold nanoflowers (Au NFs) derived from trisoctahedral (TOH) nanocrystals using D-cysteine and L-cysteine as chiral inducers. By employing a two-step seed-mediated growth approach, stable chiral Au nanoparticles with customizable sizes, shapes, and optical properties were produced by adjusting the Au nanosphere (Au NP) seed concentration and cysteine dosage. These nanoparticles exhibited optical activity in both the visible and near-infrared regions, with a maximum anisotropy factor (g-factor) of 0.024. Furthermore, the PEG-modified chiral Au NFs demonstrated excellent biocompatibility. This approach provides a precise method for geometrically controlling the design of three-dimensional chiral nanomaterials, holding great potential for biomedical applications.